What women want to hear: the helpful and unhelpful comments reported by women struggling with infertility amidst the COVID-19 pandemic - Ashley A. Balsom; Loveness Dube; Jennifer L. Gordon (PLoS ONE, 2025)
Introduction Many women struggling with infertility report that they frequently experience unhelpful social interactions with well-meaning loved ones and healthcare providers, contributing to a reluctance to confide in others about their infertility and emotional distress. However, it remains unclear what interaction content women experience as ‘helpful’ versus ‘unhelpful,’ making it difficult to provide concrete recommendations to the public about how best to support individuals struggling with infertility. Methodology Eighty women from Canada and the United States (ages 20–45 years) whose fertility treatments had been cancelled due to the COVID-19 pandemic were recruited via social media to complete an online survey, which included two open-ended questions about the most helpful and unhelpful social interactions they had had about their infertility. Two independent researchers conducted content analysis to identify categories of helpful and unhelpful social interactions. Results The following six categories were identified by women as helpful: 1) Listening, 2) Fostering hope, 3) Talking to individuals with lived experience, 4) Distraction, 5) Validating emotions, and 6) Tangible support. Responses about unsupportive interactions fell into four categories: 1) Toxic positivity, 2) Advice-giving, 3) Invalidation, and 4) Intruding. Sample quotes from each category are provided. Conclusion These findings provide valuable insights that can be used to develop future educational materials for the general public on how to interact with individuals experiencing infertility.